A clothing manufacturer uses the model a=f+4−−−−√−36−f−−−−−√ to estimate the amount of fabric to order from a mill. In the formula, a is the

Question

A clothing manufacturer uses the model a=f+4−−−−√−36−f−−−−−√ to estimate the amount of fabric to order from a mill. In the formula, a is the number of apparel items (in hundreds) and f is the number of units of fabric needed. If 4 apparel items will be manufactured, how many units of fabric should be ordered?

in progress 0
niczorrrr 1 year 2021-09-03T10:19:36+00:00 1 Answers 100 views 0

Answers ( )

    0
    2021-09-03T10:20:50+00:00

    Questions:

    A clothing manufacturer uses the model a = √(f + 4) – √(36 – f) to estimate the amount of fabric to order from a mill. In the formula, a is the number of apparel items (in hundreds) and f is the number of units of fabric needed. If 400 apparel items will be manufactured , how many units of fabric should be ordered?


    Answer:

    32 units of fabrics

    Step-by-step explanation:

    Given

    [tex]a = \sqrt{f + 4} – \sqrt{36 – f}[/tex]

    Required

    Find f when a  = 4

    Substitute 4 for a

    [tex]4 = \sqrt{f + 4} – \sqrt{36 – f}[/tex]

    Rewrite as:

    [tex]\sqrt{36 – f} + 4 = \sqrt{f + 4}[/tex]

    Square both sides

    [tex](\sqrt{36 – f} + 4)^2 = (\sqrt{f + 4})^2[/tex]

    [tex](\sqrt{36 – f} + 4)^2 = f + 4[/tex]

    [tex]36 – f + 8\sqrt{36 – f} + 16 = f + 4[/tex]

    Collect Like Terms

    [tex]8\sqrt{36 – f}= f +f+ 4 – 36 -16[/tex]

    [tex]8\sqrt{36 – f}= 2f -48[/tex]

    Divide through by 2

    [tex]4\sqrt{36 – f}= f -24[/tex]

    Square both sides

    [tex]16(36-f) = (f – 24)^2[/tex]

    [tex]16(36-f) = f^2 – 48f + 576[/tex]

    [tex]576-16f = f^2 – 48f + 576[/tex]

    [tex]-16f = f^2 – 48f[/tex]

    Collect like terms

    [tex]f^2 – 48f + 16f = 0[/tex]

    [tex]f^2 -32f = 0[/tex]

    Factorize

    [tex]f(f – 32) = 0[/tex]

    [tex]f = 0[/tex] or [tex]f = 32[/tex]

    f can not be 0 because some units must be ordered.

    So, f = 32

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )